RFID Reader Microstrip 915 MHz Design For Ticketing Highway Toll Without Tapping - Muhamad Abdul Rahman Suyudi; Bambang Setia Nugroho; Edwar Edwar (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2019)
The use of radio frequency identification (RFID) for gateless highway toll ticketing system is expected to have an excellent accuracy in detecting every passing car. Practically, a RFID reader should be able to precisely read tags installed in cars queuing in a certain lane, while avoiding any reading of car tags in other queuing lanes or outside the reader’s reading range. Therefore, a microstrip antenna for the reader is required to have a proper configuration. In this work, an RFID reader antenna microstrip, has been proposed, operating at 915 MHz and deployable at highway gates. The proposed beam width is intentionally configured to cover the width of one gate lanes, avoiding excessive coverages on other lanes. Besides, the antenna is intended to have a circular polarization, hence avoiding any reading problem despite potential tilting of RFID tag in a passing car. The resulting gain is 1.77 dB, which is expected to affect the amount of transmitting power required by an RFID transmitter. Looking at the result of this study, the proposed antenna is stated to be applicable for RFID readers at gateless highway system.